B cell analysis in SARS‐CoV‐2 versus malaria: Increased frequencies of plasmablasts and atypical memory B cells in COVID‐19. Issue 1 (4th December 2020) - Wildner, Nils H.; Ahmadi, Parimah; Schulte, Sophia; Brauneck, Franziska; Kohsar, Matin; Lütgehetmann, Marc; Beisel, Claudia; Addo, Marylyn M.; Haag, Friedrich; Schulze zur Wiesch, Julian
Abstract: B cells play a central role in antiviral and antiparasitic immunity, not only as producers of antibodies, but also as APCs and mediators of inflammation. In this study, we used 16‐color flow cytometry analysis to investigate the frequency, differentiation, and activation status of peripheral B cells of patients with SARS‐CoV‐2 infection or acute Plasmodium falciparum malaria compared with the healthy individuals. As a main result, we observed an increase of the frequency of (CD27 –, CD21 – ) atypical memory B cells and (CD19 +, CD27 +, CD38 + ) plasmablasts in malaria and COVID‐19 patients. Additionally, CD86, PD‐1, CXCR3, and CD39 expression was up‐regulated, whereas CD73 was down‐regulated on plasmablasts of COVID‐19 and malaria patients compared with the bulk B cell population. In particular, there was a more pronounced loss of CD73 + B cells in malaria. The frequency of plasmablasts positively correlated with serum levels of CRP, IL‐6, and LDH of COVID‐19 patients. In the longitudinal course of COVID‐19, a rapid normalization of the frequency of atypical memory B cells was observed. The role and function of plasmablasts and atypical memory B cells in COVID‐19 and other acute infections remain to be further investigated. The role of B cells as either "driver or passenger" of hyperinflammation during COVID‐19 needs to be clarified. Graphical Abstract: Plasmablasts and atypical memory B cells are more frequent in patients with COVID‐19 and malaria than in healthy subjects.